Metode Penelitian Ilmiah Identifikasi dan Karakterisasi Bakteri Asam Laktat pada Pekasam Asal Sarolagun Jambi - Mayla Fasha Azla; Ardi Mustakim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Pekasam fermentation is still carried out traditionally using spontaneous fermentation. Traditional fermentation products have weaknesses such as inconsistent product quality, excessive microbial growth that is difficult to control, and a low initial LAB population that causes spoilage bacteria to grow rapidly before LAB growth. These weaknesses need to be addressed to produce pekasam with good and uniform quality. One way to do this is by making pekasam on a laboratory scale by adding a starter culture of lactic acid bacteria to the fermentation process (Caterina et.al, 2025). Pekasam is made through a spontaneous fermentation process or with the help of starter cultures, namely microorganisms such as lactic acid bacteria (LAB). In traditional production, fermentation occurs naturally due to microorganisms already present in the raw materials. However, spontaneous fermentation often results in less uniform quality due to uncontrolled microbial growth and a low initial LAB population, allowing spoilage microbes to grow first.